Spaces and Places of Opera - Baker, Robert (Circuit, 2007)
AbstractSite-specific opera are those works which are either composed for, or produced in (or both) a prescribed space other than that of the opera house. The particular site chosen for the production of such a work has a profound effect on how that work of art is received. Questions are raised with regard to the work’s meaning and its relationship to the time and place of the site in which it is performed. In order to better understand the spatial and temporal richness within site-specific opera, recent productions of European and North American operas from the nineteenth and twentieth centuries are considered. Based upon composer/librettist intentions, the site of the premiere production and its relation to the music-dramatic work, five types of site-specific opera are proposed.